Avaliação do uso de membrana de polipropileno na neoformação óssea de alveolo pós-exodontia: um estudo clínico e tomográfico - Sousa, Rodolfo Nunes de (2016)
The preservation of post-extraction alveolar ridge is one of the challenges of dentistry, especially when rehabilitation claim with endosseous implants. As a result of tooth loss, the residual alveoli tends to reabsorb, creating occasions where there is need for grafting surgery to rehabilitation through supported implant prosthesis. This condition can be prevented, among other techniques, by Guided Bone Regeneration. This study aimed to evaluate the effectiveness of a non-absorbable membrane on bone healing after tooth extraction alveoli sites. A study was conducted with 18 patients requiring extraction, a total of 20 sites, prior to the installation of the implant, which sought care in Face Defects Nucleos the Federal University of Ceará. Was performed prior clinical and radiographic evaluation to surgical procedures, these were divided into two groups: the test group (n = 10) there was installation of non-absorbable membrane, and the control group (n = 10) the membrane was not used. All patients underwent computed tomography cone beam at fifteen and ninety days postoperatively. In both exams vertical and horizontal linear measurements were made through the ImageJ software, post-extraction alveolar center of fifteen and ninety days. It was observed that the retention time in the test group (0.45 ± 0.78) showed if the distance significantly greater than the height of the control group (-2.25 ± 0.97), in which can be seen a significant reduction in bone height (p <0.001). It was noted significant difference in the pattern of variation of the horizontal measured in treated groups with the membrane (0.45 ± 1.92) and control (-1.22 ± 0.49) (p=0,015). The use of non-absorbable membrane did not cause infection, swelling or allergic reaction immunoinflammatory site. The conditions evaluated, clinical and tomographic, noticed a bone maintenance height and widht of fresh alveoli sites can benefit from the installation of endosseous implants.